2016
DOI: 10.7466/jkhma.2016.34.4.157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resilience and Retirement Attitudes Perceived by Middle-aged Married Men on a Meaningful Life

Abstract: The purpose of this study is to investigate the effects of resilience and retirement attitudes perceived by middle-aged married men on a meaningful life, and provide basic data based on empirical research for reexamining meaningful lives of middle-aged married men. For the study, a survey was conducted with middle-aged men aged between 40 and 60 who were married with children and employed and live in Seoul or Gyeonggido. A total of 476 copies of data were analyzed. For the analysis, SPSS 20.0 was used to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Table 5 presents the results, which indicated that the model was statistically significant The variable with the strongest influence on meaning in life was resilience(β=.46, p<.001), followed by social support (β=.25, p<.001) and health status (β=.13, p=.041). These results support previous studies reporting that resilience significantly predicted the sense of a meaningful life 29 , and social support and meaning in life were positively correlated 4,30 .…”
Section: Resultssupporting
confidence: 91%
“…Table 5 presents the results, which indicated that the model was statistically significant The variable with the strongest influence on meaning in life was resilience(β=.46, p<.001), followed by social support (β=.25, p<.001) and health status (β=.13, p=.041). These results support previous studies reporting that resilience significantly predicted the sense of a meaningful life 29 , and social support and meaning in life were positively correlated 4,30 .…”
Section: Resultssupporting
confidence: 91%
“…Moreover, as stress or depression is a predictor of suicidal ideation (27), creating a system that can detect related symptoms and initiate timely interventions to prevent QOL impairment is necessary. Middle adulthood is characterized by an increased risk of chronic diseases (6) and deterioration in sleep quality due to andropause symptoms (29), leading to a negative view of their health and affecting QOL. This study identified factors affecting QOL in middleaged men.…”
Section: Discussionmentioning
confidence: 99%
“…They are also in a stage of transition from young adulthood to older adulthood, characterized by declining physical functions and the occurrence of various health issues, which lowers their QOL (3). Specifically, middle-aged men experience physical changes, such as andropause symptoms, due to a decrease in male hormones, aging-related changes in appearance, and chronic diseases (6). Under the burden of competition due to these changing circumstances, middle-aged men can feel a growing sense of crisis or a deterioration of their QOL (5).…”
Section: Introductionmentioning
confidence: 99%